Austria : Staff Report for the 2003 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The Austrian economy performed well, but long-term problems were unaddressed. Austria has weathered the slump well. The government's economic policy priorities and recent achievements have been commendable. Tax reform will help improve the economy's long-term growth potential. Successful reform of inter-governmental fiscal relations is key to achieving the medium-term fiscal objectives. The recent pension reform will ensure long-term sustainability of the pension system. The creation of the financial market authority has strengthened financial supervision but continued vigilance is required. The government's structural reform agenda is appropriate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet